Narcine baliensis, a new species of electric ray from southeast Asia (Chondrichthyes: Torpediniformes) - Carvalho, Marcelo R. De; White, William T. (Zootaxa, 2016)
A new species of numbfish, Narcine baliensis, sp. nov., is described from the tropical eastern Indian Ocean from Indonesia. It is superficially similar to N. brevilabiata and N. atzi in aspects of its color pattern, but is distinguished from both congeners in details of its color pattern, in tooth band morphology, and in proportions of its dorsal fins, among other features. Narcine baliensis, sp. nov., is unique in having a dorsal color pattern composed of large, circular, ovoid or elongate dark brown spots or blotches on dorsal disc along with more numerous small (about eye-sized or slightly greater) brownish, subcircular spots, with large blotches and small spots surrounded by a very slender creamy-white pattern, as well as in having broadly circular upper and lower tooth bands of about the same width and shape. The genus Narcine is now composed of 20 valid species, but uncertainty remains concerning the identification and morphological variation of some of its species in the tropical Indo-West Pacific region.